2020
DOI: 10.1093/ckj/sfaa008
|View full text |Cite
|
Sign up to set email alerts
|

Acute interstitial nephritis associated with immune checkpoint inhibitors: a single-centre experience

Abstract: Background Checkpoint inhibitors (CPIs) are used to treat solid organ metastatic malignancies. They act by triggering a vigorous immune response against tumoural cells, preventing their proliferation and metastasis. However, this is not a selective response and can cause immune-related adverse events (irAEs). The kidney can potentially be damaged, with an incidence of irAEs of 1–4%. The most frequent type of toxicity described is acute interstitial nephritis (AIN). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 15 publications
6
31
0
Order By: Relevance
“…As previously reported, subnephrotic proteinuria and pyuria were present in patients with ICI-AKI 26 , 27 and they had greater number of urinary white blood cells, red blood cells, and blood leucocyte count as compared with non–ICI-AKI. Hansel stain was not performed or was negative in most of the patients, as it is well known that its sensitivity/specificity is quite low for AIN diagnosis.…”
Section: Discussionsupporting
confidence: 77%
“…As previously reported, subnephrotic proteinuria and pyuria were present in patients with ICI-AKI 26 , 27 and they had greater number of urinary white blood cells, red blood cells, and blood leucocyte count as compared with non–ICI-AKI. Hansel stain was not performed or was negative in most of the patients, as it is well known that its sensitivity/specificity is quite low for AIN diagnosis.…”
Section: Discussionsupporting
confidence: 77%
“…In a study published in this issue, Oleas et al [ 16 ] report a single-center study of patients with nonhematologic malignancies who received ICI treatment during a 14-month period, experienced AKI (based on the Acute Kidney Injury Network criteria) and underwent a kidney biopsy at the Vall d’Hebron University Hospital, Barcelona, Spain. During this period, 826 patients with nonhematologic organ malignancies received ICI treatment and AKI occurred in 125 patients (15.1%).…”
mentioning
confidence: 99%
“…In this study, the median time from ICI initiation to AKI was 14 weeks (range 6–37) [ 18 ]. In this study, the time between the start of ICI and the onset of AKI was a mean of 5.8 months (range 2–11) [ 16 ]. In the study by Isik et al [ 17 ], AKI was found to develop earlier in the ICI-AKI patients compared with the non-ICI-AKI patients {median 4 months [95% condfidence interval (CI) 1.2–11.4] versus 8.5 months [95% CI 5.3–10.4], respectively; P = 0.026}.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This has been seen in about 2%-5% of the patients. [1][2][3][4]5 Less commonly, immune checkpoint inhibitors can lead to glomerulonephritis. 3,6,7 Renal tubular acidosis is a very rare presentation of immunerelated kidney side effects.…”
mentioning
confidence: 99%